Ketogenic diet therapy for epilepsy during pregnancy and lactation: An international survey exploring clinician perspectives - Kelly Faltersack; Tanya J. W. McDonald; Valentina De Giorgis; Bobbie Barron; Mackenzie C. Cervenka; Anita Devlin; Laura A. Healy; Magnhild Kverneland; Elles van derLouw; Mengyang Lu; Martina P. Zanaboni; Marisa Armeno; et al. (Epilepsia Open)
Abstract Objective Ketogenic diet therapies (KDTs) are increasingly used as a treatment for people with epilepsy of childbearing potential (PWECP) and glucose transporter type 1 deficiency syndrome (Glut1DS). The aim of this study was to collect information on clinical experience with KDT during pregnancy and lactation in these populations. Methods Between December 2023 and June 2024, an online survey was widely circulated to healthcare professionals (HCPs) working with PWECP and people with Glut1DS of childbearing potential on KDT. The survey explored KDT use during pregnancy and lactation. Only HCPs working with patients who expressed interest in KDT and who were planning to become pregnant or were already pregnant were invited to complete the survey. Results Thirty‐five HCPs had counseled patients about whether to follow KDT during pregnancy. Sixty percent of HCPs did not recommend KDT during pregnancy. Key concerns included a lack of expertise with KDT use during pregnancy, insufficient data on the safety of KDT use during pregnancy, and uncertainty about the impact on fetal development. Among the HCPs (40%) who recommended KDT during pregnancy, there was no consensus regarding the version of KDT or optimal macronutrient composition. Even fewer HCPs (n = 5) had provided counseling on diet adaptation during lactation. Low Glycemic Index Treatment and the modified Atkins diet were most recommended. Blood ketone monitoring was unanimously recommended during lactation. Significance Based on the survey results, HCPs have variable opinions about the safety, management, ideal diet, and levels of ketosis for people with epilepsy (PWE) and Glut1DS on KDT during pregnancy and lactation. There was consensus about monitoring ketosis levels and ensuring micronutrient supplementation. Patient enrollment in pregnancy registries that capture KDT use is crucial to support future research and expand knowledge about the safety of KDT so HCPs and PWE or Glut1DS can make informed decisions about their treatment. Plain Language Summary Most healthcare providers (HCPs) did not advise ketogenic diet therapy (KDT) for epilepsy during pregnancy, though some noted exceptions for glucose transporter type 1 deficiency syndrome. Their main concerns were not having enough information about safety for the parent and fetus and their own lack of experience using KDT during pregnancy. The 40% of HCPs who supported the use of KDT during pregnancy stressed the need for personalized care and close monitoring to reduce risks. Few HCPs have used KDT during lactation. Experts advised using more flexible versions of KDT during lactation. More research is needed.